Effect of 50% and maximal inspired oxygen concentrations on respiratory variables in isoflurane-anesthetized horses - Hubbell, John AE (BioMed Central, 2011)
BACKGROUND: The purpose of this study was to compare the effects of 0.5 fraction of inspired oxygen (FiO(2)) and >0.95 FiO(2 )on pulmonary gas exchange, shunt fraction and oxygen delivery (DO(2)) in dorsally recumbent horses during inhalant anesthesia. The use of 0.5 FiO(2 )has the potential to reduce absorption atelectasis (compared to maximal FiO(2)) and augment alveolar oxygen (O(2)) tensions (compared to ambient air) thereby improving gas exchange and DO(2). Our hypothesis was that 0.5 FiO(2 )would reduce ventilation-perfusion mismatching and increase the fraction of pulmonary blood flow that is oxygenated, thus improving arterial oxygen content and DO(2). RESULTS: Arterial partial pressures of O(2 )were significantly higher than preanesthetic levels at all times during anesthesia in the >0.95 FiO(2 )group. Arterial partial pressures of O(2 )did not change from preanesthetic levels in the 0.5 FiO(2 )group but were significantly lower than in the >0.95 FiO(2 )group from 15 to 90 min of anesthesia. Alveolar to arterial O(2 )tension difference was increased significantly in both groups during anesthesia compared to preanesthetic values. The alveolar to arterial O(2 )tension difference was significantly higher at all times in the >0.95 FiO(2 )group compared to the 0.5 FiO(2 )group. Oxygen delivery did not change from preanesthetic values in either group during anesthesia but was significantly lower than preanesthetic values 10 min after anesthesia in the 0.5 FiO(2 )group. Shunt fraction increased in both groups during anesthesia attaining statistical significance at varying times. Shunt fraction was significantly increased in both groups 10 min after anesthesia but was not different between groups. Alveolar dead space ventilation increased after 3 hr of anesthesia in both groups. CONCLUSIONS: Reducing FiO(2 )did not change alveolar dead space ventilation or shunt fraction in dorsally recumbent, mechanically ventilated horses during 3 hr of isoflurane anesthesia. Reducing FiO(2 )in dorsally recumbent isoflurane anesthetized horses does not improve oxygenation or oxygen delivery.